Análise acústico-comparativa de vogais do português brasileiro com vogais do inglês norte-americano - Miranda, Irma Iunes (2012)
This experiment, through the acoustic analysis of vowel sounds, investigated the vowel system used by Capixabas and compared it to the American English vowel system. Another purpose consisted of describing the Capixaba vowel system. As part of this investigation, the vowel system from Vitória was compared to the results obtained in a former experiment in which the vowel systems from five other capital cities were investigated. A gender comparison was made to complement the description of the Capixaba vowel system. Each group of speakers was composed of four men and four women, who had already graduated or were still in college. All the Brazilian speakers were born in Vitória and all the American speakers were born in Kansas and lived in Lawrence. All of them belonged to the age range from 20 to 40. In both dialects the sentences carrying the key words were recorded randomly and, later, each vowel was recorded 10 times. Words carrying the vowels to be investigated provided a similar phonetic context. Vowel sounds can be described by the frequencies of the two first formants (F1 and F2). These formants result from the vocal tract shape, more specifically the position of the lips and tongue (vertical and horizontal dimensions) at the moment of the vowel production. Due to the great difficulty in describing the position of the tongue at the moment of the production of a vowel, it is necessary to observe the given distances between the vowels that make up the repertoire of a particular speaker. These distances can be estimated by plotting the acoustic measurements of each vowel on the graph of the formant frequencies F1xF2. F1 and F2 are related to the vertical and horizontal tongue positions during the vowel production. The free software Akustyk/Praat is responsible for the frequency analysis. The Lobanov normalization method was applied in order to compensate for the physiological differences between speakers and statistical analyses were used to identify distinct groups. The absolute distinction between Brazilian Portuguese (BP) and American English (AE) vowel systems was confirmed and the lack of distinction between the vowels [?] and [?] was observed in the dialect from Kansas. Symmetry was found in the Capixaba triangular system, since the front vowels and the corresponding back vowels have the same height. The distinctions between genres for high vowels were detected in the dialect from Vitória. The proximity of the Carioca system for [i,e,?], the Recifense system for [?,a], the Paulista system for [o] and the Gaúcho system for [u] are the results of the comparison between the Capixaba system and other five Brazilian capital cities. The results of the comparison between BP and AE systems can contribute to studies of Applied Linguistics devoted to the teaching of foreign languages. The acoustic description of the Capixaba vowel system will add to other research and contribute towards revealing the characteristics of Capixaba speech. The results obtained through this experiment will be able to support other experiments that concern Brazilian Portuguese and studies of foreign language acquisition.